Management Character Education in Kindergarten - Sobarna, Ayi; Hakim, Arif (Universitas Negeri Semarang, 2017)
Experts agree that character education should start at an early age. However, implementation is often found irregularities. The Ministry of Education and Culture has appointed a number of kindergarten as a pilot project for the implementation of character education. This article reports how the management of character education in kindergarten to be the pilot project. By using a qualitative approach, which attempts to understand the specific situation with the case study method, it was found that kindergarten pilot project has been implemented in an integrated character education in learning through the development of habituation and specialized in the development of a learning theme. Planning the character education program is integrated in the weekly planning (RKM) and daily planning (RKH) and not in the form of an independent program. Implementation of the the character education program conducted through the internalization of the values of the characters in the learning activities using the model in groups with children as a center of learning (student centered). Assessment being applied on character education programs in kindergarten pilot project have not been using special instruments, but still combined with the assessment of child development in general (moral and religious, physical and motor, cognitive, linguistic, social and emotional child). One of the recommendation of this study is the kindergarten should start developing assessment instruments which are specialized in assessing development of learners.